Combined transepicardial and transseptal implantation of autologous CD 133+ bone marrow cells during bypass grafting improves cardiac function in patients with low ejection fraction. Issue 4 (12th February 2020) - Soetisna, Tri Wisesa; Sukmawan, Renan; Setianto, Budhi; Mansyur, Muchtaruddin; Murni, Tri Wahyu; Listiyaningsih, Erlin; Santoso, Anwar
Abstract: Objectives: Autologous CD133+ bone marrow stem cells may improve cardiac function. This randomized, single‐blind clinical trial inquired whether a combined transepicardial and transseptal implantation of CD133+ stem cells during coronary artery bypass grafting (CABG) improve cardiac function with ejection fraction (EF) changes as a primary endpoint in patients with low EF. Methods: Thirty patients with coronary heart disease and EF <35% were randomized to undergo CABG alone or CABG with transseptal and transepicardial implantation of CD133+. Cardiac function was evaluated using cardiac magnetic resonance imaging (MRI) before and 6 months after CABG. Results: Preoperative EF was lower in the intervention group (25.88% ± 5.66%) than in the control group (30.18% ± 3.85%; P  = .04). The adverse event incidence was similar between both groups. At 6 months, EF changes were significantly higher (8.69% ± 9.49; P  = .04) in the CD133+ group than in the CABG‐only group. Compared to the control group, significant improvements were seen in the wall motion score index ( P  = .003) and scar size proportion ( P  = .047) in the CD133+ group. The quality of life (QOL), assessed by a 6‐minute walking test, showed considerable improvement in the CD133+ group compared to that in the control group ( P  = .03). The Minnesota Living with Heart Failure Questionnaire (MLHFQ) scale did not show improvement in the intervention group ( P  = .09, vs control). Conclusion: Combined transepicardial and transseptal autologous CD133+ BMC implantation during bypass grafting improved cardiac function in low EF coronary artery disease patients.